Identification and detection of bioactive compounds in Linum usitatissimum (Flaxseed) and its antibacterial properties against selected oral pathogens - Fadzir, Ummu Afifah; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Darnis, Deny Susanti (2017)
Despite the tremendous advancement in medical field, oral infections are still considered as one of the major public health problems suffered by human population; causing a burden to health care system worldwide. Apart from using synthetic antibiotics, anti-bacterial agents from natural resources are suggested as an alternative for the treatment of infectious diseases due to lesser side effects imposed. Flaxseed (Linum usitatissimum) has been shown to demonstrate some anti- bacterial properties. However, its effects towards oral pathogens are still limited. Hence, the present study aimed to investigate the anti-bacterial effects of flaxseed extracts against selected oral pathogens. Non-polar and polar extracts of flaxseed; n-hexane, dichloromethane (DCM) and methanol (MeOH), were prepared by sequential extraction using soxhlet extraction method. The anti-bacterial activities of flaxseed extracts with different concentration (5, 7, 10, 12 & 15 μl/disc) were evaluated against three oral pathogens; Streptococcus pyogenes, Streptococcus mutans and Enterococcus faecalis using disc diffusion method. Additionally, extracts which exhibited significant diameter of inhibition zone were screened through GC-MS (n-Hexane & DCM) or LC-MS (MeOH) to detect the presence of bioactive compound. Polar extract (methanolic extract) demonstrated significant antibacterial activity (p< 0.05) against all tested oral pathogens which is comparable with the zone of inhibition exhibited by penicillin (positive control). In contrast, n-hexane and DCM extracts demonstrated variable anti-bacterial activities. GC-MS screening showed the presence of some fatty acids in n-hexane and DCM extracts. And in LC-MS screening demonstrated the presence of linolenic acid, secoisolariciresinol diglycoside, (-)-secoisolariciresinol-4-O-β-D-glucopyranoside E-p-coumaric acid, and flavone,5,7-dihydroxy-4′-O-α-D-glucoside which may have contributed greatly to the inhibitory activity of the methanolic plant extract. From the study, it can be concluded that methanolic extract of L. usitatissimum exhibited the best inhibitory activity at 15 μl/disc on S. pyogenes, S. mutans and E. faecalis.